Negotiating trade-offs in dam development in the Mekong: Implications for fisheries and fishery-based livelihoods - Friend, R.M.; Blake, D.J.H. (IWA Publishing, 2009)
A revitalised hydropower development narrative is emerging in the Mekong in which the concept of ‘trade-offs’ plays a central role. The importance of and risks to capture fisheries in the Mekong is such that any degradation has huge social, economic and environmental implications. While potential impacts of hydropower development on capture fisheries are acknowledged in this emerging narrative, it is argued that these are less than anticipated previously, that impacts can be assessed, mitigation measures introduced and trade-offs negotiated. The concept of trade-offs has an immediate appeal but it is also problematic. It draws attention away from considering development objectives and options towards focusing on impacts, and infers a technical approach as opposed to a political process of decision making. This paper draws on anthropological approaches to development policy to consider the implications of a hydropower narrative based on trade-offs in light of experience in the Mekong Basin, and to consider alternative ways of framing debate on hydropower and capture fisheries.